Strategies for Improving Teacher Competence Through Local Cultural Approaches and Digital Literacy - Nurbayani, Nunung Siti; Hardhienata, Soewarto; Wulandari, Dian (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
This study employs a mixed-methods sequential exploratory approach using the POP-SDM (Modeling and Optimization of Human Resource Management Strengthening) method to improve teacher performance as a key determinant of educational quality in vocational education. The research population consists of all civil servant teachers working at Centers of Excellence Vocational High Schools in Banten Province, Indonesia. A sample of 254 teachers from 28 schools was selected using proportional random sampling. Data were collected through document analysis, interviews, questionnaires, and observations. Qualitative data were analyzed using thematic analysis to identify key performance indicators, while quantitative data were analyzed using path analysis and POP-SDM optimization analysis to test the constellation model and research hypotheses. The findings indicate that optimal strategies for improving teacher performance involve maintaining strong performance indicators while systematically strengthening weaker ones. Priority improvement areas include knowledge acquisition, knowledge processing, knowledge distribution, communication ethics, and work quantity. This study contributes a data-driven and systematic framework for enhancing teacher performance, particularly in vocational education contexts aligned with industry needs.